Tutor on software design / Fariza Halim - Fariza, Halim (2004)
Tutor on Software Design is a system that helps users design their own software using the Unified Modeling Language (UML). The UML diagrams involved are the use case diagram, Class diagram, and sequence diagram. It is a stand-alone system that requires operating system Windows 98 or above. This report especially focuses on designing software using sequence diagram. The system receives requirements using step-by-step wizard-like method. The requirements (called as elements) include actor, use case, association, class, object and sequence of events in the exact order. After all elements are entered, the system produces a professional looking sequence diagram. The produced diagram could be edited by users and saved. This system provides a lot of information, tips, tutorial and help regarding the system usage and sequence diagram that can be accessed any time.